Molten Pool Behaviors in Double-Sided Pulsed GMAW of T-Joint: A Numerical Study - Haicang Zhang; Chunsheng Wang; Sanbao Lin (Metals, 2021)
The T-joint is one of the essential types of joints in aluminum welded structures. Double-sided welding is a preferable solution to maintain high efficiency and avoid significant distortion during T-joint welding. However, interactions between double-sided molten pools make flow behaviors complicated during welding. Numerical simulations regarding molten pool behaviors were conducted in this research to understand the complex flow phenomenon. The influences of wire feed rates and torch distances were simulated and discussed. The results show that droplet impinging drives the fluid to flow down to the root and form a frontward vortex. Marangoni stress forces the fluid to form an outward vortex near the molten pool boundary and flatten the concave-shaped molten pool surface. With an increased wire feed speed, the volume of the molten pool increases, and the root fusion is improved. With an increased torch distance, the width of the front molten pool decreases while the length increases, and the rear molten pool size decreases slightly. Both wire feed speeds and the torch distances have limited influences on the basic flow characteristics.